2001
DOI: 10.1002/mus.1051
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolic economy is inversely related to exercise intensity and type II myofiber distribution

Abstract: It is not known what causes the well-established inverse relationship between whole-body exercise economy and exercise intensity. The purpose of this study was to: (1) evaluate muscle exercise economy at 45%, 70%, and maximum isometric strength using 31P magnetic resonance spectroscopy (31P-MRS); and (2) determine the relationship between percent type II muscle fiber cross-section, whole-body exercise economy, and muscle exercise economy. Subjects included 32 premenopausal women. Muscle exercise economy was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 30 publications
3
45
2
Order By: Relevance
“…Under such isometric conditions, we did not observe a difference in economy between young and older healthy groups. Therefore, it seems likely that in older healthy individuals, the neural and mechan- ical factors involved in dynamic movements may be an important source of inefficiency, consistent with previous reports (34,54). In addition, the greater overall energy cost of dynamic compared with isometric contractions (69) may also contribute to these differences between studies, although this hypothesis awaits further testing.…”
Section: Metabolic Economy During Voluntary Contractionssupporting
confidence: 66%
See 2 more Smart Citations
“…Under such isometric conditions, we did not observe a difference in economy between young and older healthy groups. Therefore, it seems likely that in older healthy individuals, the neural and mechan- ical factors involved in dynamic movements may be an important source of inefficiency, consistent with previous reports (34,54). In addition, the greater overall energy cost of dynamic compared with isometric contractions (69) may also contribute to these differences between studies, although this hypothesis awaits further testing.…”
Section: Metabolic Economy During Voluntary Contractionssupporting
confidence: 66%
“…Although data from electrically stimulated contractions consistently indicate higher ATP cost as stimulation frequency increases (2,17,20), the impact of voluntary contraction intensity on ME is less clear. Some reports suggest a positive relationship between voluntary contraction intensity and ME (70), while other reports suggest a negative relationship (34), and still others report no change in economy across intensities (3,63). In the current investigation, muscle ME did not differ across intensities during shortduration contractions of the ankle dorsiflexor muscles.…”
Section: Metabolic Economy During Voluntary Contractionscontrasting
confidence: 52%
See 1 more Smart Citation
“…We have previously shown that type I muscle fiber is related to walking economy as well as 31 P magnetic resonance spectroscopy measured muscle metabolic economy, probably because individuals who have a higher percentage of type I muscle fibers will be less dependent on inefficient type II muscle fibers when performing any physical task. 40 However, the limited available data on muscle fiber type in Blacks suggests that if an ethnic difference exists in fiber type between Black and White subjects, Black subjects would tend to have a higher percentage of inefficient type II muscle fibers. [34][35][36] Therefore, it is unlikely that ethnic fiber type differences can explain the differences in exercise economy between the Black and White women.…”
Section: Discussionmentioning
confidence: 99%
“…Although some results suggest that mechanical factors have an important role in controlling the expression of contractile proteins [7], the influence of the quantity and type of mechanical loading on muscle is still unknown. It has been suggested that changes in muscle structure, mass, and MyHC concentration and its isoform expression, induced by a high-resistance weight-training programme, are a result of the frequency of contraction [14,22,44]. There is no explicit understanding of how the intensity of RT change the composition of MyHC isoforms.…”
Section: Discussionmentioning
confidence: 99%